Knowledge Configuration about Ciletuh UNESCO Global Geopark in Mass Media - Eli Jamilah Mihardja; Prima Mulyasari Agustini; Guson P Kuntarto (Ikatan Sarjana Komunikasi Indonesia, 2020)
This study intends to describe the discourse of the geopark in Indonesia in the Indonesian media. Media coverage is a form of knowledge in society, including about geopark in the context of sustainable regional development. Data was obtained based on analysis of media content (local and national) during 2019 and analyzed. by using sociology knowledge approach of discourse. As a result, the mass media, as a source of knowledge in society, should be able to play a greater role in providing understanding to audiences about the geopark and aspects of sustainable regional development.